EDITORIAL: INDIVIDUALIDADE CIENTÍFICA? - Guimarães, Ana Tereza Bittencourt; Grassiolli, Sabrina (Varia Scientia - Ciências da Saúde, 2022)
Editorial do Volume 8, Número 2, da Revista Varia Scientia-Ciências da Saúde